2009
DOI: 10.1038/jcbfm.2009.32
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β Signaling Alters Substrate Permeability and Tight Junction Protein Expression at the Blood-Brain Barrier during Inflammatory Pain

Abstract: Our laboratory has shown that peripheral inflammatory pain induced by λ-carrageenan (CIP) can increase blood–brain barrier (BBB) permeability and alter tight junction (TJ) protein expression leading to changes in BBB functional integrity. However, the intracellular signaling mechanisms involved in this pathophysiologic response have not been elucidated. Transforming growth factor (TGF)-β signaling pathways are known to regulate vascular integrity and permeability. Therefore, we examined the function of TGF-β s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
151
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(157 citation statements)
references
References 41 publications
5
151
1
Order By: Relevance
“…21 Furthermore, we have shown that SB431542 does not affect TGF-b/ALK1 signaling, data that emphasize the specificity of this small molecule for the TGF-b/ALK5 signaling pathway. 21 Our current study also identifies TGF-b/ALK5 signaling as a target for pharmacological manipulation of brain microvascular permeability to neuroprotective and/or antioxidant drugs for treatment of diseases with an H/R component. Targeting the TGF-b signaling pathway may enable 'tighter control' of Oatp1a4 functional expression, thereby enabling increased delivery of drugs to the brain.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…21 Furthermore, we have shown that SB431542 does not affect TGF-b/ALK1 signaling, data that emphasize the specificity of this small molecule for the TGF-b/ALK5 signaling pathway. 21 Our current study also identifies TGF-b/ALK5 signaling as a target for pharmacological manipulation of brain microvascular permeability to neuroprotective and/or antioxidant drugs for treatment of diseases with an H/R component. Targeting the TGF-b signaling pathway may enable 'tighter control' of Oatp1a4 functional expression, thereby enabling increased delivery of drugs to the brain.…”
Section: Discussionmentioning
confidence: 66%
“…At the BBB, only two ALK receptors (i.e., ALK1 and ALK5) have been identified. 21 We have previously shown that pharmacological inhibition of TGF-b/ALK5 signaling can increase Oatp1a4 functional expression. 19 Therefore, targeting of TGF-b/ ALK5 signaling during H/R provides an opportunity to control Oatp1a4 expression/activity at the BBB for optimization of CNS drug delivery.…”
Section: Introductionmentioning
confidence: 97%
“…5B). Because TGF-␤ signaling is deregulated during inflammatory pain (44,45), we assessed whether thermal pain response in Tgfbr1 cKO mice are affected after experimental inflammation induced by intraplantar carrageenan injection. We injected carrageenan into the left and vehicle into the right hind paws of 1-month-old Tgfbr1 cKO and control mice, and then we measured paw withdrawal latency at 5 and 24 h after injection.…”
Section: Decreased Cdk5 Activity and Attenuated Responses To Thermal mentioning
confidence: 99%
“…In the brain, the inhibition of TGFb type I ALK5 receptors also increases leakage (of the blood brain barrier), accompanied by changes in the expression of tight junction adhesion proteins (Ronaldson et al, 2009).…”
Section: Tgfb Regulates Vascular Homeostasis and The Response To Tissmentioning
confidence: 99%